Identifying Critical Factors for Implementing Unmanned Aerial Vehicle in Warehouse using a Newly Hybrid Decision-Making Method - Wudhikarn, Ratapol; Malang, Chommaphat (Decision Making: Applications in Management and Engineering, 2024)
Unmanned Aerial Vehicles have been broadly implemented and applied to the Supply Chain Management domain. However, its applicability in warehouse management is still in the early stages, and the influence of UAV adoption needs to be extensively explored. The successful implementation of this innovative technology depends on various influential factors that require systematic processes and techniques for a more precise investigation. This study aims to identify critical factors for implementing UAVs in warehouse management. The proposed method integrates the Delphi technique, best-worst method, decision-making trial and evaluation laboratory, and analytic network process to improve deficiencies of traditional and improved forms of multi-criteria decision-making. Two major factors, Operation and Technology, and ten sub-factors were identified. The method was applied to recognize the most critical factor of UAV adoption in warehouse management and provides a foundation for future research and practitioners to put deep concern on those factors.